Data warehouse automation trick or treat? - Oliveira, Paula Alexandra Pereira de (2020)
Data warehousing systems have been around for 25 years playing a crucial role in collecting data and transforming that data into value, allowing users to make decisions based on informed business facts. It is widely accepted that a data warehouse is a critical component to a data-driven enterprise, and it becomes part of the organisation’s information systems strategy, with a significant impact on the business. However, after 25 years, building a Data Warehouse is still painful, they are too time-consuming, too expensive and too difficult to change after deployment. Data Warehouse Automation appears with the promise to address the limitations of traditional approaches, turning the data warehouse development from a prolonged effort into an agile one, with gains in efficiency and effectiveness in data warehousing processes. So, is Data Warehouse Automation a Trick or Treat? To answer this question, a case study of a data warehousing architecture using a data warehouse automation tool, called WhereScape, was developed. Also, a survey was made to organisations that are using data warehouse automation tools, in order to understand their motivation in the adoption of this kind of tools in their data warehousing systems. Based on the results of the survey and on the case study, automation in the data warehouses building process is necessary to deliver data warehouse systems faster, and a solution to consider when modernize data warehouse architectures as a way to achieve results faster, keeping costs controlled and reduce risk. Data Warehouse Automation definitely may be a Treat.